Analisis Manajemen Badan Usaha Milik Pesantren (BUMP) Dalam Pemenuhan Kebutuhan Santri di Pesantren Hubulo Gorontalo - Ahmad Fauzi; Muh. Arif (Al-Buhuts, 2020)
This article aims to reveal how the management analysis of Pesantren-Owned Enterprises (BUMP) in meeting the needs of students at the Pesantren Hubulo Bone Bolango Regency. The method used in this research is a qualitative method with a descriptive approach. The research informants were the Boarding School Leaders, Head of Islamic Boarding Schools (BUMP), Secretary of Boarding Schools (BUMP), Shop employees in Boarding Schools (BUMP) and Consumers (santri). The results showed the Pesantren-Owned Shop Business Entity (BUMP) in meeting the needs of santri in Hubulo Pesantren is inseparable from the well-organized and well-organized management function. Starting from the management functions planing (planning), organizing (organizing), actuating (mobilizing), and controlling (controlling). Planning includes budget planning, planning to meet the needs of students and shopping planning. Organizing includes organizing employees, organizing goods, and organizing needs. While the implementation includes the implementation of the needs of students. Then supervision includes supervision of the needs of students and supervision of employees. The implementation of management functions in Pesantren-Owned Shop Business Entities in Hubulo Pesantren is carried out, so that it can be seen that the fulfillment of the needs of students runs well.